A Comparative Study of Income Disparities and Fertility Trends in Egypt - Sarg, Abdullah M (المجلة العلمية للدراسات والبحوث المالية والتجارية: علمية محكمة., 2024)
This research paper presents a comprehensive literature review of the relation between income and fertility all over the world and a comparative analysis of income disparities and fertility trends in Egypt, utilizing data from health survey for the Egyptian households and central agency for public mobilization and statistics. the study investigates the individual and socio-contextual determinants of low fertility rates and decomposes wealth-based inequality to identify points of intervention for policy development, using the last 14 years from 2008 up to December 2022 via Egypt demographic health survey (EDHS). it's clear that the fertility rates go down with a rapidly rates over all the governorates at the same time with low households' income. as a result, the Arab republic of Egypt lies in the fourth stage with regards to the relation between income and fertility which stated that (after a decreasing from the stage number two) low income is correlated with high fertility in the last 14 years.